Seroprevalences of vector-transmitted infections of small-holder dairy cattle in coastal Kenya - Maloo, S.H.; Thorpe, W.R.; Kiio, G.; Ngumi, P.; Rowlands, G.J.; Perry, Brian D. (Elsevier, 2001)
A cross-sectional study was carried out from July to September 1989 in Kaloleni Division, Coast Province, Kenya to estimate the prevalence of vector-transmitted diseases in small-holder dairy cattle and to identify the risk factors associated with different management systems. One hundred and thirty of the 157 herds with dairy cattle in Kaloleni Division were surveyed. These were from three agro-ecological zones (coconut¯cassava, cashewnut¯cassava and livestock¯millet), comprised two management systems (stall-feeding and herded grazing) and were herds with either dairy cattle only or with Zebu and dairy cattle. A formal questionnaire sought answers to questions on cattle health and management practices. A total of 734 dairy and 205 Zebu cattle in 78 dairy and 52 mixed (dairy and Zebu) herds were sampled and screened for haemoparasites (Trypanosoma, Anaplasma, Babesia, and Theileria infections). Sera were tested for antibodies to Theileria parva, using the schizonts-antigen indirect fluorescent-antibody (IFA) test and to antibodies for Babesia bigemina and antigens to Anaplasma marginale by enzyme-linked immunosorbent assay (ELISA). Packed-cell volume (PCV) also was measured. Tick-control measures were practised by all except three of the farmers. Despite this, overall seroprevalence to T. parva was >70% suggesting either that control practices were not strictly implemented or they were ineffective. The seroprevalence of T. parva in adult cattle kept in stall-feeding systems in the coconut¯cassava zone was significantly lower (57±8% (S.E.)) than in herded-grazing systems (79±3%) and there was no association between antibody prevalence and age of cattle in this zone. Antibody prevalences in cattle in the cashewnut¯cassava and the drier livestock¯millet zone increased with age. Cattle in herded-grazing systems had an overall lower seroprevalence of T. parva infection in the livestock¯millet zone (45±6%) than in the other two zones. Analysis was confined to the coconut¯cassava zone for B. bigemina and to the coconut¯cassava and cashewnut¯cassava zones for A. marginale. Mean prevalences of B. bigemina were 40.9±9 and 73±6% for dairy cattle under stall-feeding and herded-grazing systems, respectively, and increased with age. Antigen prevalences of A. marginale were over 80% in all age groups of cattle in the coconut¯cassava and cashewnut¯cassava zones. Overall trypanosome prevalence in cattle was <1%. Trypanocidal treatment was uncommon. The variations in antibody prevalence associated with risk factors such as feeding system, agro-ecological zone and age of animal suggest that management system influenced exposure to tick-borne infection (particularly, T. parva infections) in small-holder dairy cattle in coastal Kenya.